Are Protective Activities and Limitations in Practical Skills of Daily Living Associated with the Cognitive Performance of People with Mild Cognitive Impairment? Baseline Results from the BrainFit-Nutrition Study - Scheerbaum, Petra; Grässel, Elmar; Bösl, Sophia; Hanslian, Etienne; Kessler, Christian S.; Scheuermann, Julia-Sophia (Nutrients, 2023)
Limitations in daily living have not yet been described adequately for mild cognitive impairment (MCI). In this study, we investigated first, time spent on protective activities (social, mental, and physical) and second, limitations in practical skills of daily living, both for people with MCI. We used baseline data from 270 individuals who participated in the randomized controlled trial BrainFit-Nutrition. The Montreal Cognitive Assessment (MoCA) was used to identify people with MCI. Participants were asked how much time they spent engaged in social, mental, and physical activities each week. Furthermore, the Bayer-ADL scale was used to quantify deficits in activities of daily living (ADLs). Regarding protection, the number of hours spent engaged in the three activity areas was significantly correlated with the cognitive performance in people with MCI. Social activities were positively associated with current cognitive performance. Concerning the limitations in practical skills of daily living, older and more cognitively impaired individuals were affected. Memory and orientation appear to be among the first practical skills of daily living that become impaired in people with MCI. Treatment recommendations for people with MCI include an increase in social, mental, and physical activities as well as the promotion of a healthy lifestyle.
CRIS-Team Scopus Importer:2023-09-08
Keywords: chronic diseases; dementia; integrative medicine; lifestyle medicine; mild cognitive impairment

Computerised cognitive training tools and online nutritional group counselling for people with mild cognitive impairment: study protocol of a completely digital, randomised, controlled trial. - Scheerbaum, Petra; Book, Stephanie; Jank, Michael; Hanslian, Etienne; Dello'Ro, Melanie; Schneider, Julia; Scheuermann, Julia-Sophia; Bösl, Sophia; Jeitler, Michael; Kessler, Christian; Grässel, Elmar (BMJ Open, 2022)
INTRODUCTION: People with mild cognitive impairment (MCI) are at increased risk of decreasing cognitive functioning. Computerised cognitive training (CCT) and nutrition have been shown to improve the cognitive capacities of people with MCI. For each variable, we developed two kinds of interventions specialised for people with MCI (CCT: 'individualised' CCT; nutrition: a whole-food, plant-based diet). Additionally, there are two kinds of active control measures (CCT: 'basic' CCT; nutrition: a healthy diet following the current guidelines of the German Nutrition Society). The aim of this study is to investigate the effects of the two interventions on cognition in people with MCI in a 2×2 randomised controlled trial with German participants. METHODS AND ANALYSIS: Participants will be community-dwelling individuals with a psychometric diagnosis of MCI based on the Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination. With N=200, effects with an effect size of f≥0.24 (comparable to Cohen's d≥0.48) can be detected. Screening, baseline, t6 and t12 testing will be conducted via a videoconferencing assessment, telephone, and online survey. Participants will be randomly allocated to one of four groups and will receive a combination of CCT and online nutritional counselling. The CCT can be carried out independently at home on a computer, laptop, or tablet. Nutrition counselling includes 12 online group sessions every fortnight for 1.5 hours. The treatment phase is 6 months with follow-ups after six and 12 months after baseline. ETHICS AND DISSEMINATION: All procedures were approved by the Friedrich-Alexander-Universität Erlangen-Nürnberg Ethics Committee (Ref. 21-318-1-B). Written informed consent will be obtained from all participants. Results will be published in peer-reviewed scientific journals, conference presentations. TRIAL REGISTRATION NUMBER: ISRCTN10560738.
EVALuna2:505254

Manchmal trink ich auch Wasser… – Alkoholkonsum von Menschen mit leichter kognitiver Beeinträchtigung - Donath, Carolin; Grässel, Elmar; Scheuermann, Julia-Sophia; Bösl, Sophia; Scheerbaum, Petra (Psychiatrische Praxis, 2023)
Aim Risky alcohol consumption increases the risk of dementia for people with mild cognitive impairment (MCI). The aim of this study is to assess alcohol consumption in people with MCI. Methods Socio-demographics, 12-month prevalence, 30-d prevalence, prevalence of risky consumption ( > 10 g/20 g/d pure alcohol for women/men) and binge drinking (≥ 50 g pure alcohol on one occasion) were recorded in 270 people (≥ 60 years) with MCI from the German RCT "Brainfit-Nutrition" in 2022. Results Approximately half of the people with MCI (50.8 %) drink at least once a week. About one fifth (17.0 %) of participants met the criterion for binge drinking; every third woman (34.8 %) and every fifth man (18.6 %) crossed the line to risky consumption in the last 30 d. Discussion Generally, people with MCI show similar consumption prevalence as the 65 + German general population. However, the prevalence of risky consumption in women with MCI is significantly higher.
CRIS-Team Scopus Importer:2023-09-22
Keywords: alcohol abstinence; alcohol drinking; binge drinking; cognitive dysfunction; sociodemographic factors

Motivational interviewing training for caregiver counsellors: Study protocol of a mixed-methods evaluation using the Kirkpatrick model - Schmidt, Johanna; Bösl, Sophia; Lauer, Natascha; Grässel, Elmar; Henßler, Oliver Timo; Pendergrass, Anna (BMJ Open, 2025)
Introduction Caring for a relative in the home environment is a great challenge for many informal caregivers (CGs). Caregiver counselling offers support to the CGs and can, thus, help them improve CGs' burdensome home care situations, especially if the caregiver counsellors (CCs) have good communication skills. Motivational interviewing (MI) has the potential to further enhance the communication skills of CCs and the effectiveness of MI has been demonstrated internationally in a wide variety of contexts. However, MI has not been implemented and evaluated in the caregiver counselling context yet. Methods and analysis The goals of our prospective, interventional, mixed-methods study are the development, implementation and evaluation of a training course for CCs on the topic of 'Motivational Interviewing for caregiver counselling' in Germany. The training is specifically adapted to the caregiver counselling context and consists of an e-Learning, an on-site workshop and a voluntary follow-up support phase. Its quality and benefits will be evaluated according to Kirkpatrick's four-level evaluation model. Measured outcomes will be participants' satisfaction with the training (level I: reaction), MI knowledge (level II: learning), perceived use (level III: behaviour) and counselling competence, self-efficacy, social cognitions about the use of MI and perceived impact of MI (level IV: results). Primary outcome is counselling competence measured by Counsellor Activity Self-Efficacy Scale. The data will be collected at baseline (t 0), after the on-site workshop (t 1), after the voluntary follow-up support (t 2) and 6 months after the training (t 6). Quantitative data will be analysed with several repeated-measures ANOVAs and qualitative data with qualitative content analysis. Recruitment is ongoing until 31 July 2024. Ethics and dissemination All procedures were approved by the Ethics Committee of the Friedrich-Alexander University Erlangen-Nürnberg (project number 24-108-B). Informed consent will be obtained before participants are enrolled. Serious adverse events are not expected. Results will be published in peer-reviewed journals and presented at conferences. Trial registration number ISRCTN14218056.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Caregiver Burden; Caregivers; Psychosocial Intervention; Quality in healthcare

My patient might be depressed – can I still screen for MCI? Exploring cognitive performance on the MoCA in older people screened for depressive symptoms with the PHQ-9 - Bösl, Sophia; Scheerbaum, Petra; Grässel, Elmar; Kessler, Christian; Scheuermann, Julia-Sophia (BMC Geriatrics, 2025)
Objective: The aim of this study was to compare the Montreal Cognitive Assessment (MoCA) performances of people who report no, subclinical, and clinical symptoms of depression. Methods: Data was collected for the randomized controlled trial BrainFit-Nutrition. A secondary data analysis of 1,111 participants (age ≥ 60 years; M = 68.4 years; 55.1% female) was performed. Depressive symptoms were assessed with the Patient Health Questionnaire-9 (PHQ-9), cognitive performance was assessed via the MoCA. Performance differences were tested with Kruskal-Wallis tests. Two sensitivity analyses were conducted, one with data from people with MCI and one with the original item structure of the MoCA. Results: No differences were found in the MoCA total score or in visuospatial, executive functioning, attention, memory, or orientation subscores between individuals with no, subclinical, or clinical symptoms of depression. A sensitivity analysis also showed no differences. Conclusion: Cognitive screening with the MoCA seems to be robust against depression and could therefore be used to screen for MCI regardless of depression level. Trial registration: The study was prospectively registered at the International Standard Randomized Controlled Trial Number Registry on 23/11/2021 (ISRCTN 10560738).
CRIS-Team Scopus Importer:2025-05-30
Keywords: Cognitive performance; Depressive symptoms; MoCA; Older people

Tagespflege: Wer nutzt sie und wer möchte sie nutzen? Multivariable Analyse der aktuellen und zukünftigen Inanspruchnahme der Tagespflege bei der häuslichen Pflege - Bösl, Sophia; Diehl, Kristina; Pendergrass, Anna; Grässel, Elmar (Gesundheitswesen, Supplement, 2024)
Background Adult day care serves to ease the burden on informal caregivers and to provide adequate care and support for care recipients. Across Bavaria and Germany, adult day care is attended by 4 % of all care recipients. The aim of the secondary analysis was to identify variables linked to the current or desired future use of adult day care services. Methodology For the cross-sectional study Benefits of Being a Caregiver (“Zugewinne durch die Pflege”), informal caregivers of geriatric care receiver were surveyed in Bavaria from October 2019 to March 2020 (age > 65; n = 958). Data regarding caregiving situation, characteristics of informal caregivers and care recipients, and sociodemographic information were collected. Two binary logistic regression analyses were conducted to identify predictors of current or desired adult day care service use. Results Adult day care was used by 7.3 % (n = 70) of informal caregivers. Utilization was associated with dementia and high care degree requirements of the care recipient(Nagelkerke's R2 = 0.200). Of the 888 informal caregivers not using adult day care services, 223 (25.1 %) expressed a desire to use them. This was associated with care recipients suffering from dementia, a poor previous relationship, and a high subjective burden on the informal caregiver (Nagelkerke’s R2 = 0.083). Conclusion The utilization rate of adult day care was found to be higher than reported in Bavarian or German care statistics. Dementia and an increased need for care of the care recipient were associated with utilization, but contrary to reports in literature, no association with everyday limitations, sex, education, or duration of care was found. More than two-thirds of Bavarian informal caregivers do not want to use adult day care services either now or in the future.
CRIS-Team Scopus Importer:2024-03-08
Keywords: adult day care centers; care recipient; informal caregivers; long-term care